Ex Post Destruction in the Hold-up Problem - WANG, Huan (Institutional Knowledge at Singapore Management University, 2013)
We investigate whether or not ex post destruction can solve the hold-up problem. After clarifying the difference between ex post destruction and nontrade when negotiation breaks down, we show that the option of ex post destruction is not sufficient to enhance ex ante efficiency. In particular, only if the information about the spitefulness of the supplier is coarse enough, will the option of ex post destruction alleviate the inefficiency of underinvestment caused by the hold-up problem.